2004
DOI: 10.1097/01.tp.0000101495.22734.07
|View full text |Cite
|
Sign up to set email alerts
|

A randomized long-term trial of tacrolimus/sirolimus versus tacrolimus/mycophenolate mofetil versus cyclosporine (NEORAL)/sirolimus in renal transplantation. Ii. Survival, function, and protocol compliance at 1 year

Abstract: This 1-year interim analysis of a long-term, prospective, randomized renal-transplant study indicates that decreasing maintenance dosage of Tacro with adjunctive Siro or MMF appears to point to improved long-term function, with reasonably few adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 16 publications
5
119
0
1
Order By: Relevance
“…15 Numerous single-center reports describe sirolimus/tacrolimus-based immunosuppression in organ transplant recipients. [17][18][19][20][21][22][23][24][25] Consistent with the findings of our study, a retrospective analysis by El-Sabrout et al 19 emphasized the use of sirolimus loading doses to increase rejection-free survival. In a pilot study of early tacrolimus withdrawal, Grinyo et al reported improved renal function and blood pressure in patients randomly assigned to a regimen of tacrolimus withdrawal versus those who remained on standard-dose tacrolimus and sirolimus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…15 Numerous single-center reports describe sirolimus/tacrolimus-based immunosuppression in organ transplant recipients. [17][18][19][20][21][22][23][24][25] Consistent with the findings of our study, a retrospective analysis by El-Sabrout et al 19 emphasized the use of sirolimus loading doses to increase rejection-free survival. In a pilot study of early tacrolimus withdrawal, Grinyo et al reported improved renal function and blood pressure in patients randomly assigned to a regimen of tacrolimus withdrawal versus those who remained on standard-dose tacrolimus and sirolimus.…”
Section: Discussionsupporting
confidence: 88%
“…16 There is an expanding body of literature on the successful clinical application of the combination of sirolimus-and tacrolimusbased immunosuppression in renal and nonerenal allograft recipients. [17][18][19][20][21][22][23][24][25] In an attempt to minimize the toxicity of tacrolimus, this study was designed to investigate the clinical safety and efficacy of a regimen of sirolimus plus reduced-dose tacrolimus (rTAC) in renal allograft recipients.…”
mentioning
confidence: 99%
“…Large clinical trials did not reveal any increase in the incidence of posttransplantation diabetes among patients who were treated with sirolimus (13-16), either alone or in combination with CNI, although recent investigations have challenged this conclusion (38,39). In the above studies, however, posttransplantation diabetes has been defined and recognized only by the patient's requirement for insulin.…”
Section: Discussionmentioning
confidence: 90%
“…As previously reported, [15][16] between May 2000 and December 2001, 150 recipients between 14 to 78 yr of age, of either deceased donor(DD) or non-HLA identical living donor (LD) first kidney transplants, were randomized immediately before transplantation into one of three study groups (the center institutional review board approved the protocol; patients gave written informed consent before enrollment): TAC/SRL, TAC/MMF, and CSA/SRL. In each arm, the CNI was not started until renal function had improved (serum creatinine concentration (Cr) Ͻ4 mg/dl absent dialysis).…”
Section: Concise Methodsmentioning
confidence: 99%
“…[15][16][17] In the present report, we compare, at a median follow-up of eight years post-transplant, the efficacy/ safety of TAC in decreasing maintenance dosage combined with SRL versus MMF (TAC/SRL versus TAC/MMF), and CSA in decreasing maintenance dosage combined with SRL (CSA/ SRL) in adult primary-kidney-transplant recipients.…”
mentioning
confidence: 99%